Development of methods for spawning, fertilization, larval husbandry, and settlement in the temperate coral Astrangia poculata - E. M. Borbee; I. Changsut; J. S. McAlister; T. Demarco; S. W. Davies; C. F. Ianniello; M. Sánchez García; L. M. Roberson; A. Schickle; J. M. Sneed; G. Pelose; D. Wuitchik; et al. (Frontiers in Marine Science, 2026)
The temperate coral Astrangia poculata has recently emerged as a useful experimental organism for studying symbiosis, organism-environment interactions, and embryonic development. Crucial to the success of establishing any species as a laboratory animal are reliable husbandry protocols and the ability to culture the full life cycle in captivity. Here, we detail efforts resulting from several years (2016-2025) of collaboration by a multi-institutional group of researchers toward standardized and reproducible methods for A. poculata spawning, fertilization, larval husbandry, and settlement in the laboratory. Spawning in A. poculata can be reliably induced in the laboratory via thermal treatment, and the methods presented here yielded laboratory fertilization rates of up to 93%. Unfed larvae exhibit rates of development comparable to previous reports, and larvae supplemented with commercially available organic matter sources, including Reef Roids and Reef Snow, exhibited signs of accelerated development. Settlement (attachment and metamorphosis) of A. poculata larvae was achieved using tetrabromopyrrole (TBP), a small molecule previously shown to induce settlement and/or metamorphosis in several tropical coral species. The methods described here, including augmentation of A. poculata larval culture with feed, and TBP-triggered settlement, represent a necessary first step for culturing A. poculata individuals throughout the life cycle, which can be scaled and adapted to enable new lines of inquiry dependent on experimental manipulation of specific genetic host lineages, and/or early life stages.

Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Cross-system transfer of fatty acids from aquatic insects supports terrestrial insectivore condition and reproductive success - Catrin F. Eden; Richard K. Broughton; Bart Donato; Chris M. Hewson; Caroline Isaksson; Stuart P. Sharp (Oecologia, 2025)
Cross-system fluxes of aquatic insects rich in omega-3 long-chain polyunsaturated fatty acids (ω-3 LC-PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may subsidise insectivorous vertebrates that are suffering due to terrestrial insect declines. The benefits of high ω-3 LC-PUFA diets, such as improved growth and immunocompetence, have previously been demonstrated for riparian insectivores. Understanding the potential for aquatic insects to benefit a range of species is necessary for informing land management practices. Using the spotted flycatcher ( Muscicapa striata ), a habitat-generalist, insectivorous bird as a model, we tested how blood plasma ω-3 LC-PUFA concentrations and the ratio of ω-6:ω-3 fatty acids were related to the body condition of 14 adults and 84 chicks in the wild. We measured how variation in ω-3 LC-PUFAs and ω-6:ω-3 was related to river proximity, to test whether they were related to aquatic insect availability. We assessed how these relationships may extend beyond the individual level by monitoring flying insect availability throughout two breeding seasons and testing its ability to predict reproductive success. EPA was positively correlated with body condition in chicks and adults and declined with distance from a river. Conversely, ω-6:ω-3 was negatively correlated with body condition and increased with distance from a river. Breeding success was positively correlated with aquatic insect availability, suggesting that access to a high ω-3 LC-PUFA diet has the potential to mitigate declines in generalist insectivores. Our results highlight how the maintenance or creation of high-quality freshwater habitats may be promoted in a conservation context for non-riparian species.

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

COVID-19 Pandemic Telemedicine Compared to Pre-pandemic In-person Delivery of the New Direction® Program for Weight Loss Success - H. Saroka; J. Schwartz; K. Sharp; J. Ponce; C. Hanson; M. Timmerman; M. Jackson (Journal of the Academy of Nutrition and Dietetics, 2024)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Exposure to global change and microplastics elicits an immune response in an endangered coral - Colleen B. Bove; Katharine Greene; Sharla Sugierski; Nicola G. Kriefall; Alexa K. Huzar; Annabel M. Hughes; Koty Sharp; Nicole D. Fogarty; Sarah W. Davies (Frontiers in Marine Science, 2023)
Global change is increasing seawater temperatures and decreasing oceanic pH, driving declines of coral reefs globally. Coral ecosystems are also impacted by local stressors, including microplastics, which are ubiquitous on reefs. While the independent effects of these global and local stressors are well-documented, their interactions remain less explored. Here, we examine the independent and combined effects of global change (ocean warming and acidification) and microplastics exposures on gene expression (GE) and microbial community composition in the endangered coral Acropora cervicornis . Nine genotypes were fragmented and maintained in one of four experimental treatments: 1) ambient conditions (ambient seawater, no microplastics; AMB); 2) microplastics treatment (ambient seawater, microplastics; MP); 3) global change conditions (warm and acidic conditions, no microplastics; OAW); and 4) multistressor treatment (warm and acidic conditions with microplastics; OAW+MP) for 22 days, after which corals were sampled for genome-wide GE profiling and ITS2 and 16S metabarcoding. Overall A. cervicornis GE responses to all treatments were subtle; however, corals in the multistressor treatment exhibited the strongest GE responses, and genes associated with innate immunity were overrepresented in this treatment. ITS2 analyses confirmed that all coral were associated with Symbiodinium ‘fitti’ and 16S analyses revealed similar microbiomes dominated by the bacterial associate Aquarickettsia , suggesting that these A. cervicornis fragments exhibited remarkably low variability in algal and bacterial community compositions. Future work should focus on functional differences across microbiomes, especially Aquarickettsia and viruses, in these responses. Overall, results suggest that when local stressors are coupled with global change, these interacting stressors present unique challenges to this endangered coral species.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Development and molecular cytogenetic characterization of Thinopyrum bessarabicum introgression lines in hexaploid and tetraploid wheats - Amit K. Singh; Peng Zhang; Chongmei Dong; Jianbo Li; Smriti Singh; Richard M. Trethowan; Peter J. Sharp (Theoretical and Applied Genetics, 2020)

Peptide Inhibitor of Complement C1 (PIC1) Inhibits Growth of Pathogenic Bacteria - Pamela S. Hair; Magdielis Gregory Rivera; Adrianne I. Enos; Susan E. Pearsall; Julia A. Sharp; Nazita Yousefieh; Frank A. Lattanzio; Neel K. Krishna; Kenji M. Cunnion (International Journal of Peptide Research and Therapeutics, 2019)

Understanding Climate Adaptation on Public Lands in the Upper Midwest: Implications for Monitoring and Tracking Progress - Christine M. Anhalt-Depies; Tricia Gorby Knoot; Adena R. Rissman; Anthony K. Sharp; Karl J. Martin (Environmental Management, 2016)

Peristalsis with Oscillating Flow Resistance: A Mechanism for Periarterial Clearance of Amyloid Beta from the Brain - M. Keith Sharp; Alexandra K. Diem; Roy O. Weller; Roxana O. Carare (Annals of Biomedical Engineering, 2016)

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

Identification and imaging of soil and soil-pile deformation in the presence of liquefaction - M. Zeghal; P. V. Kallou; C. Oskay; T. Abdoun; M. K. Sharp (Earthquake Engineering and Engineering Vibration, 2006)

Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort - F. Denk; M. E. Walton; K. A. Jennings; T. Sharp; M. F. S. Rushworth; D. M. Bannerman (Psychopharmacology, 2005)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Effect of antidepressant drugs on dopamine D 1 and D 2 receptor expression and dopamine release in the nucleus accumbens of the rat - K. Ainsworth; S. E. Smith; T. S. C. Zetterström; Q. Pei; M. Franklin; T. Sharp (Psychopharmacology, 1998)

Infection of specific-pathogen free lambs with a herpesvirus isolated from pulmonary adenomatosis - F. M. M. Scott; J. M. Sharp; K. W. Angus; E. W. Gray (Archives of Virology, 1984)

Rapid transmission of sheep pulmonary adenomatosis (jaagsiekte) in young lambs - J. M. Sharp; K. W. Angus; E. W. Gray; F. M. M. Scott (Archives of Virology, 1983)